Risk Factor for Anxiety on Clients with Diabetic Foot Ulcer (Indian Journal of Public Health Research & Development, 2020)
Anxiety is one of the psychological responses experienced by clients with diabetic ulcers that can affectglycemic control, serious complications, foot self-care behavior and slow the wound healing process. Thisresearch used to find out the factors that influence anxiety in clients with diabetic ulcers. This study wasa retrospective analysis using medical records and diagnostic results of diabetic ulcers at Haji GeneralHospital, Surabaya, Indonesia. The sample was 951 people suffering from diabetic ulcers between January2014 - December 2018. Samples were diagnosed with anxiety based on nursing diagnoses and fulfillinginclusion and exclusion criteria. The multivariable model of diabetic ulcer client anxiety was generatedusing stepwise logistic regression. There were independent variables affecting the anxiety of diabetic ulcerclients namely wound type (p < 0.015; OR = 0.91), health insurance (p
Keywords: Predictive, Risk Factor, Diabetic foot ulcer, Anxiety.